An Analysis on the Wasiyyah Muslim Property in Malaysia - Mohd Noor, Nor Adila; Mahamood, Siti Mashitoh; Mohd Noor, Nor Azlina; Ismail, Che Zuina (Online Journal of Research in Islamic Studies, 2019)
When a person dies, all assets under his name will be frozen and cannot be transacted. The consequences are that, from legal perspective, the deceased assets can only be transacted when his personal representative applies to a letter of representation from the Civil High Court. In Malaysia, a person may die testate or intestate. The former means that the person who died leaving a will and the latter means that the person who died without leaving any testamentary document resulted to the operation of law of intestacy to Non-Muslim and law of Faraid to the Muslim. This article will deliberate on the current law Muslim testate succession in Malaysia. This article adopts the doctrinal analysis by examining the existing primary and secondary materials gathered from multiple sources including statutory, and case law. This article concludes that there is still lacuna in the law regarding Muslim testate estate. This article acknowledges that the law relating to inheritance in Malaysia is divided into two namely substantive law according to the religion of deceased and procedural law which under the purview of federal statutes. If the Syariah High Court is serious to regulate the Muslim testate matters, each and every state legislature in West Malaysia must legislate a written law on Muslim testate succession.